Regulation Implementation Effectiveness of Outdoors Users in Town Square of Bandung, Indonesia - Harum Bunga Melati (Journal of Contemporary Governance and Public Policy, 2020)
Bandung Square in Indonesia is a public outdoors that has many visitors from various regions. One of the parts that make up Bandung town square is sign boards as a symbol of written rules that all square visitors must obey. The background of this research is that Bandung town square is equipped with a lot of sign boards with different rules in every corner. Besides, civil service police units and public protection officers also take part in guarding around Bandung town square, so the researcher want to know more about the implementation of the rules contained in the Bandung town square because the researcher still found several violations. This study aims to determine the regulation implementation effectiveness of outdoors users in town square of Bandung. The advantages of this goal are as a reflection for social institutions in maintaining public regulation and as a reminder to town square visitors to be more obedient to the rules that applied to maintain comfort. This type of research is a qualitative research conducted using descriptive methods. Research data were collected using interviews with instruments in the form of questions about the subject matter. The data collected was described using qualitative-descriptive analysis. Based on data findings in the field, it shows that the implementation of the regulation in Bandung town square is quite effective, because there are still some violations found and their social institutions are still less firm and conducive in carrying out social control there. So, public order still has not been achieved according to the expected goals.